ANALISIS PENERAPAN ARSITEKTUR WIRELESS LAN MENGGUNAKAN TOP DOWN APPROACH PADA PT. TELKOM PONTIANAK - Sandy Kosasi (STMIK PONTIANAK, 2011)
Abstracts: Implementation of LAN Technologies Choices model using Top-Down Approach method in analyzing the application of wireless LAN network architecture shows that the use of wireless LAN architecture has more benefits with lower cost and higher speeds than dial-up technology . But the application still raises many issues, especially regarding the stability of the existing network system is still not smooth and often drop out (no connection), access speed decreases or tends to decline over time usage, the number of complaints from stakeholders are also increasing rapidly, internet access often unstable and can thus disrupt the smooth work. Therefore, the improvement and enhancement of information technology needs to be done on an ongoing basis to always to meet the needs of the market and understand the behavior of stakeholders in using Internet services. Always measure the performance of information technology for wireless LAN networks to align with business needs. Provide assurance or guarantee smoothness, reliability, and trust and satisfaction in using the technology offered.Keywords : Wireles LAN, LAN Technologies Choices, Top-Down Approach, Business and IT Alignment